2017
DOI: 10.1063/1.4996579
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of spacer-less and spacer-filled reverse electrodialysis

Abstract: Reverse electrodialysis (RED) is a renewable energy technology used to recover dissipated chemical energy in river estuaries globally. This technology has recently attracted significant attention owing to its great reliability and scalability. In this study, we propose the use of a spacer-less RED (i.e., a system in which a woven mesh is excluded from the flow channel). The performance of spacer-less RED, including its gross power density, internal resistance, and hydraulic loss, is compared with that of the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…By using the current membranes, the power density generated by RED is reported between 0.17 W/m 2 and 4.32 W/m 2 . 82−86 Apart from the fabrication of IEMs, a number of studies have been conducted to develop the RED stack, such as design new stack configuration and spacer, 87,88 investigate the composition of anolyte/catholyte, and develop novel electrodes. 89,90 However, the use of natural waters (like seawater and surface water) may consume more energy by transporting of water and pretreatment to control membrane fouling and spacer blockage.…”
Section: Energy Recovery By Red or Ddpowermentioning
confidence: 99%
See 1 more Smart Citation
“…By using the current membranes, the power density generated by RED is reported between 0.17 W/m 2 and 4.32 W/m 2 . 82−86 Apart from the fabrication of IEMs, a number of studies have been conducted to develop the RED stack, such as design new stack configuration and spacer, 87,88 investigate the composition of anolyte/catholyte, and develop novel electrodes. 89,90 However, the use of natural waters (like seawater and surface water) may consume more energy by transporting of water and pretreatment to control membrane fouling and spacer blockage.…”
Section: Energy Recovery By Red or Ddpowermentioning
confidence: 99%
“…Various investigations have been done by using different kinds of salts as high salinity streams in RED processes. Development of IEMs with lower ohmic resistance is one of the key points to generate a higher power density. By using the current membranes, the power density generated by RED is reported between 0.17 W/m 2 and 4.32 W/m 2 . Apart from the fabrication of IEMs, a number of studies have been conducted to develop the RED stack, such as design new stack configuration and spacer, , investigate the composition of anolyte/catholyte, and develop novel electrodes. , …”
Section: Energy Recovery By Red or Ddpowermentioning
confidence: 99%
“…The choice of salts in these processes depends on the solubility, the resistivity and the amount of heat required [ 2 ]. Ammonium bicarbonate-based reverse electrodialysis (AmB RED) is one such system that has shown potential in developing feasible closed-loop systems [ 3 , 9 , 10 ]. An example of such an AmB RED system that uses waste heat to generate hydrogen is depicted in Figure 1 .…”
Section: Introductionmentioning
confidence: 99%
“…The first experimental concept of RED was developed by Pattle (in the 1950s), using alternating chambers of fresh and saline water separated by acidic and basic membranes [10]. However, not until recently have there been active theoretical, numerical, and experimental investigations aiming at pilot projects [11,12], efficient membrane materials [13][14][15][16][17][18][19][20][21][22], improved large-scale cell designs [22][23][24][25][26][27][28], and better understanding of the underlying mechanisms at pore-scale charged interfaces [29][30][31] for optimal power outputs [1,17,32,33]. However, it is challenging to carry out rigorous theoretical and numerical analyses to fully compute and accurately predict the electric outputs of a RED system.…”
Section: Introductionmentioning
confidence: 99%
“…To optimize large-scale implementation of RED or blue energy technology using membranes, as a top-down approach, multiple compartment RED cells have been constructed [28,56,57]. Recent studies have shown several crucial influences of ion-exchange membranes [3,58,59] of different materials (e.g., microfiltration [60], polymeric [15,61,62], graphene [18,20], Nafion [13,63]), surface charges, and pore-size distributions, electrolyte solutions (e.g., types of ions [64][65][66], multivalent ions [67], ion concentrations), as well as hydrodynamics affected by the flow configurations [68] and cell designs through separators' dimensions [23][24][25][26]. Typical power density outputs measured with various ion exchange membrane stacks ranged from 0.13 to 2.48 W m −2 [32].…”
Section: Introductionmentioning
confidence: 99%